How long do floods throughout the millennium remain in the collective memory? - Fanta, Václav; Šálek, Miroslav; Sklenicka, Petr (Nature communications, 2019)
Is there some kind of historical memory and folk wisdom that ensures that a community remembers about very extreme phenomena, such as catastrophic floods, and learns to establish new settlements in safer locations? We tested a unique set of empirical data on 1293 settlements founded in the course of nine centuries, during which time seven extreme floods occurred. For a period of one generation after each flood, new settlements appeared in safer places. However, respect for floods waned in the second generation and new settlements were established closer to the river. We conclude that flood memory depends on living witnesses, and fades away already within two generations. Historical memory is not sufficient to protect human settlements from the consequences of rare catastrophic floods.
Keywords: History, 16th Century; History, 20th Century; History, 18th Century; History, Medieval; lidé; dějiny 15. století; Memory; dějiny 20. století; záplavy; emigrace a imigrace; folklór; Folklore; dějiny středověku; History, 19th Century; Disasters; katastrofy; dějiny 18. století; History, 17th Century; History, 21st Century; paměť; Emigration and Immigration; dějiny 19. století; dějiny 17. století; dějiny 16. století; Floods; dějiny 21. století; History, 15th Century; Humans